Injury incidence and risk factors in youth soccer players: a systematic literature review. Part II: Intrinsic and extrinsic risk factors - Mandorino, M.; Figueiredo, A. J.; Gjaka, M.; Tessitore, A. (Biology of Sport, 2023)
Injury is defined as a complex phenomenon determined by the non-linear interaction of several intrinsic and extrinsic factors. The objective of the present study was to perform a systematic literature review on the injury risk factors in young soccer players. After electronic database searching, articles in line with the inclusion criteria were selected for the systematic review. Injury risk factor data were extracted and grouped in intrinsic and extrinsic risk factors. The main findings of the current review are as follows: (1) alteration in neuromuscular control such as limb asymmetry and dynamic knee valgus are important intrinsic risk factors; (2) maturation status may impair neuromuscular control and increase the risk of injury; (3) fatigue and poor recovery contribute to the onset of overuse injuries; (4) the impact of anthropometric factors is still unclear; (5) previous injuries increase the risk of re-injuries; (6) highly skilled players are more exposed to risk of injuries; (7) high external workloads increase the risk of injuries; (8) playing position, as well as sport specialization, exposes young soccer players to greater injury risk. Many factors (e.g., neuromuscular control, training load, maturity status) can modify the susceptibility to injury in young soccer players. Being aware of the complex interaction between these factors is essential to identify players at higher risk of injury, develop adequate prevention strategies, and from a scientific point of view move from a reductionist to a complex system approach.